Cu(II)-enhanced degradation of acid orange 7 by Fe(II)-activated persulfate with hydroxylamine over a wide pH range. (January 2020) - Liu, Xin; Yuan, Baoling; Zou, Jing; Wu, Lingbin; Dai, Lin; Ma, Hongfang; Li, Kai; Ma, Jun
Abstract: The activation of persulfate by Fe(II) coupled with hydroxylamine (the HA/Fe(II)/PS system) was highly effective for the degradation of refractory organic contaminants under acidic pH conditions. However, owing to the precipitation of ferric hydroxide and/or the slow reduction from Fe(III) to Fe(II), the HA/Fe(II)/PS system was invalid under neutral and alkaline pH conditions. In this study, it was observed that the degradation of acid orange 7 (AO7) was strongly enhanced over the wide pH range of 2–9 when trace Cu(II) (0.5–5 μM) was spiked into the HA/Fe(II)/PS system. It was evident that Cu(I) was generated via the reduction of Cu(II) by HA in the bimetallic system at both pH 3 and pH 8, and the steady concentration of Fe(II) in the bimetallic system was much higher than that in the HA/Fe(II)/PS system due to the rapid reaction between Fe(III) and Cu(I). Quenching experiments using tert-butyl alcohol, methanol and sodium bromide as the scavengers and electron spin resonance experiments confirmed that the primary reactive species responsible for AO7 degradation were sulfate radical at both pH 3 and pH 8, rather than hydroxyl radical and Cu(III). Nevertheless, sulfate radical was mainly produced by Fe(II)-activated PS at pH 3, while both Cu(I) and Fe(II) made important contributions to the generation of sulfate radical at pH 8. The bimetallic system was also highly effective in degrading other organic contaminants, such as phenol, diclofenac, reactive red 2 and orange G. This study might provide a promising idea based on Fe(II)-activated PS for degrading organic contaminants over a wide pH range. Graphical abstract: Image 1 Highlights: The degradation of AO7 was strongly enhanced by adding trace Cu(II) in the HA/Fe(II)/PS system. The redox cycle of Fe(III)/Fe(II) was promoted by adding trace Cu(II) in the HA/Fe(II)/PS system. The bimetallic system was highly effective in degrading pollutants in the wide pH range of 2–9. Sulfate radical was identified as the primary reactive species in the bimetallic system.